Cancer-Associated Fibroblasts from Lung Tumors Maintain Their Immunosuppressive Abilities after High-Dose Irradiation - Gorchs, Laia; Hellevik, Turid; Bruun, Jack-Ansgar; Camilio, Ketil-Andre; Al-Saad, Samer; Stuge, Tor-Brynjar; Martinez-Zubiaurre, Inigo (Frontiers in Oncology, 2015)
Accumulating evidence supports the notion that high-dose (>5 Gy) radiotherapy (RT) regimens are triggering stronger pro-immunogenic effects than standard low-dose (2 Gy) regimens. However, the effects of RT on certain immunoregulatory elements in tumors remain unexplored. In this study we have investigated the effects of high-dose irradiation (HD-RT) on the immunomodulating functions of cancer-associated fibroblasts (CAFs). Primary CAF cultures were established from lung cancer specimens derived from patients diagnosed for non-small cell lung cancer. Irradiated and non-irradiated CAFs were examined for immunomodulation in experiments with peripheral blood mononuclear cells from random, healthy donors. Regulation of lymphocytes behavior was checked by lymphocyte proliferation assays, lymphocyte migration assays and T-cell cytokine production. Additionally, CAF-secreted immuno-regulatory factors were studied by multiplex protein arrays, ELISAs and by LC-MS/MS proteomics. In all functional assays we observed a powerful immuno-suppressive effect exerted by CAF-conditioned medium on activated T-cells (p>0,001), and this effect was sustained after a single radiation dose of 18 Gy. Relevant immuno-suppressive molecules such as prostaglandin E2, interleukin-6 and -10, or transforming growth factor-β were found in CAF conditioned medium, but their secretion was unchanged after irradiation. Finally, immunogenic cell death responses in CAFs were studied by exploring the release of high motility group box-1 and ATP. Both alarmins remained undetectable before and after irradiation. In conclusion, CAFs play a powerful immuno-suppressive effect over activated T-cells, and this effect remains unchanged after HD-RT. Importantly, CAFs do not switch on immunogenic cell death responses after exposure to HD-RT.